2019 IEEE/CVF Conference on Computer Vision and Pattern Recognition (CVPR) 2019
DOI: 10.1109/cvpr.2019.00853
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Attention Memory Network for Movie Story Question Answering

Abstract: This paper proposes the progressive attention memory network (PAMN) for movie story question answering (QA). Movie story QA is challenging compared to VQA in two aspects: (1) pinpointing the temporal parts relevant to answer the question is difficult as the movies are typically longer than an hour, (2) it has both video and subtitle where different questions require different modality to infer the answer. To overcome these challenges, PAMN involves three main features: (1) progressive attention mechanism that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 27 publications
(71 reference statements)
0
59
0
Order By: Relevance
“…denotes the frame number. Following [20,26], we also use detected object labels (referred to as visual concept) instead of ImageNet features as visual input on the TVQA dataset (see Table 1).…”
Section: Input Embeddingmentioning
confidence: 99%
See 4 more Smart Citations
“…denotes the frame number. Following [20,26], we also use detected object labels (referred to as visual concept) instead of ImageNet features as visual input on the TVQA dataset (see Table 1).…”
Section: Input Embeddingmentioning
confidence: 99%
“…With the development of deep learning techniques (e.g., neural memory networks [15], attention mechanisms [28]), studies on QA have been rapidly advanced, and showed prominent performance improvement. In this paper, we focus on the video story QA task [20,23,36], which distinctively requires machines to understand the video contents and storylines based on temporally-aligned videos and subtitles, and thus answer multiple choice questions correctly. An example of video story QA can be seen in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations